Correlation of Sedentary Lifestyle and Interest in Physical Education Learning among Adolescents - Wibisono, I Gusti Ananda Bayu; Birawa, Chandra; Wicaksana, Amrih Ibnu; Priambodo, Anung (Physical Activity Journal (PAJU), 2024)
This study determined the correlation between sedentary activities and interest in Physical Education learning in adolescents. Correlational analysis was utilized in this study, with a sample of 33 students obtained using an accidental sampling technique. The research instrument used an ASAQ questionnaire to acquire sedentary activity data and a learning interest questionnaire that had been tested for validity and reliability values of 0.801> 0.60. The results revealed that the sedentary activity of watching videos/DVDs was the highest, with an average duration of 95.09 minutes/day, and the sedentary activity of reading for pleasure was the lowest, with an average duration of 19.91 minutes/day. Meanwhile, the average interest in Physical Education learning is medium. The product-moment correlation test showed that the Pearson correlation value is -0.350, so it can be concluded that sedentary activities and interest in Physical Education learning have a significant negative correlation. The result stated that the highest sedentary activities had the lowest learning interest.